Of reindeer and man, modern and Neanderthal: A creation story founded on a historic perspective on how to conserve wildlife, woodland caribou in particular - Geist, Valerius (Rangifer, 2003)
A review of successful systems of wildlife conservation, the North American included, suggests that broad public support and determined effort by volunteers is essential for wildlife conservation. Since North American wildlife conservation is the only large-scale system of sustainable natural resource use, and exemplifies the great economic and cultural benefits of a renewable resource held in common, its lessons may be profitably applied to Rangifer conservation. Animals that have value are surrounded by myths that tell of their relationship to humans. In our Anglo-American culture reindeer and caribou are rather deficient in this respect. However, reindeer feature prominently in the rise of modern humans and the demise of Neanderthal man early in the Upper Paleolithic. The colonization by humans of the periglacial environments during the last glaciation depended on the rich periglacial megafauna, Rangifer included. Archeological sites of the European Upper Paleolithic show that reindeer were the most important food source. The Upper Paleolithic, characterized by exceptional physical development and health of people, as well as by the first flowering of art, extended from Spain to Crimea with surprisingly little cultural change for some 25 000 years. While the cave paintings express an infatuation with dangerous game (woolly mammoth, woolly rhino, steppe wisent, giant deer, cave lions, bears etc), the archeological sites indicate that reindeer was the staple food. Reindeer play a minor role in cave art. Neither this art, nor archeological sites, show any evidence of warfare. It is hypothesized that during a mid-glacial interstadial modern people entered Europe having developed a highly successful system of hunting reindeer using interception based on the discovery of chronologic time. This led to a first flowering of culture based on a rich economy, but also to additional hunting mortality of the periglacial mega-herbivores that Neanderthal people depended on. That would explain the slow decline into extinction of the previously invincible Neanderthal people. Therefore, modern humans owe much of what they are to reindeer. We need to reciprocate. What is urgently required is a foundation formed by volunteers for the conservation of caribou, similar to the Rocky Mountain Elk Foundation, focusing on the severely endangered wood¬land caribou.
Keywords: reindeer; caribou; caribou conservation; cave art; extinction; megafauna; Rangifer tarandus; Upper Paleolithic; stone age